2019
DOI: 10.3389/fgene.2019.00699
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Genomic Characteristics and Selection Signatures in Korean Indigenous Goats Through Comparison of 10 Goat Breeds

Abstract: Indigenous breeds develop their own genomic characteristics by adapting to local environments or cultures over long periods of time. Most of them are not particularly productive in commercial terms, but they have abilities to survive in harsh environments or tolerate to specific diseases. Their adaptive characteristics play an important role as genetic materials for improving commercial breeds. As a step toward this goal, we analyzed the genome of Korean indigenous goats within 10 goat breeds. We collected 136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…There were two out-of-range findings of Y1B, in the Uganda Karamonja and in the Korean native breeds. Because of the popularity of Swiss dairy goats in both Uganda (NAADS, 2005) and Korea (Kim et al, 2019), crossbreeding again is the most likely explanation.…”
Section: Resultsmentioning
confidence: 99%
“…There were two out-of-range findings of Y1B, in the Uganda Karamonja and in the Korean native breeds. Because of the popularity of Swiss dairy goats in both Uganda (NAADS, 2005) and Korea (Kim et al, 2019), crossbreeding again is the most likely explanation.…”
Section: Resultsmentioning
confidence: 99%
“… 1 Inbreeding coefficient was estimated using a method of moments. 2 The genomic characteristics in these breeds was identified by Badr Benjelloun et al in 2019 [ 2 ]. …”
Section: Figurementioning
confidence: 99%
“…Domestic goats play an important role in the transition of human civilization from foraging and hunting to farming and herding by supplying milk, meat, and fiber. Due to natural and anthropogenic factors (e.g., climate changes, human migration, and population expansion), there are now more than 1006 million individuals and 557 registered breeds worldwide [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goats are important husbandry animals with an ancient domestication history and economic value. It has been reported that their domestication occurred approximately 10,000 years ago and spread worldwide following human migrations and trade routes ( Benjelloun et al, 2015 ; Kim et al, 2019 ). China is the global leader in terms of goat production ( Skapetas and Bampidis, 2016 ), including many commercial, indigenous, and composite breeds.…”
Section: Introductionmentioning
confidence: 99%